БИЛИМЛАРНИ СУСТ ЎЗЛАШТИРУВЧИ ТАЛАБАЛАР ДИҚҚАТИНИНГ АСОСИЙ МОҲИЯТЛАРИ - Ҳайитов, Қ.Қ. (SCIENCE and SOCIETY, 2024)
This article focuses on the factor of “attention” and its mechanisms, which is one of the pressing problems of our time, which is part of the characteristics of poorly adaptive students.